2008
DOI: 10.1111/j.1467-9280.2008.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Stored Word Sequences in Language Learning

Abstract: Recent accounts of the development of grammar propose that children remember utterances they hear and draw generalizations over these stored exemplars. This study tested these accounts' assumption that children store utterances as wholes by testing memory for familiar sequences of words. Using a newly available, dense corpus of child-directed speech, we identified frequently occurring chunks in the input (e.g., sit in your chair) and matched them to infrequent sequences (e.g., sit in your truck). We tested you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(169 citation statements)
references
References 35 publications
14
140
1
2
Order By: Relevance
“…This finding is in line with previous studies in the field of language production that have examined the impact of phrase frequency on measures of phonological reduction [26], and agrees with findings from the field of language comprehension [17,[20][21][22][23][24][25]. For example, as discussed in the Introduction, Arnon and Snider [17] found that recognition times of multi-word phrases were sensitive to the frequency with which the phrases appeared in the language.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is in line with previous studies in the field of language production that have examined the impact of phrase frequency on measures of phonological reduction [26], and agrees with findings from the field of language comprehension [17,[20][21][22][23][24][25]. For example, as discussed in the Introduction, Arnon and Snider [17] found that recognition times of multi-word phrases were sensitive to the frequency with which the phrases appeared in the language.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, a study by Sosa and MacFarlane [21] revealed that the speed with which listeners were able to detect the word 'of' was determined by the frequency of the phrase in which the word appeared. Finally, Bannard and Matthews [22] have shown that two and three-year old infants are better at repeating and producing high (e.g., 'sit in your chair') versus low (e.g., 'sit in your truck') frequency phrases (see [23][24][25] for additional results). Thus, there now exists a substantial body of evidence that suggest that phrase frequency affects the processing of multi-word phrases in a language comprehension context.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable evidence also exists in the child processing literature. Bannard and Matthews (2008) found that young children processed frequent phrases (a drink of milk) faster than infrequent ones (a drink of tea). This lead them to conclude that children have experience-derived knowledge of four-word utterances, the most frequent of which are stored in their lexicon.…”
Section: Discussionmentioning
confidence: 99%
“…If the child did so, we also considered whether they used the same one as the experimenter or another form (e.g., 'muddy shoes' instead of 'dirty shoes'). Using the same adjective should be easier if it is frequent given the noun (Bannard & Matthews, 2008) and this should act as a counter pressure in production.…”
Section: Information Content and Ease Of Productionmentioning
confidence: 99%